التكايا السودانية كداعم للنازحين في مناطق النزاع التي تعاني من نقص السيولة النقدية: التمويل بالغذاء والدواء دراسة حالة اجتماعية - Mahmoud Mohamed Ali Mahmoud Edris; Mohamad Aniq Aiman Alias (Faculty of Syariah and Law, USIM, 2026)
This study aims to highlight the role of Sudanese takāyā as key providers and supporters of internally displaced persons (IDPs) by supplying food, clothing, medicines, voluntary donations, and zakat funds in conflict-affected areas experiencing severe cash shortages due to sieges and the displaced population’s fear of ongoing military confrontations. The study addresses the scarcity of adequate financial resources available to support displaced and besieged communities, which adversely affects their ability to move freely, secure livelihoods, and meet their basic needs. Employing a descriptive–analytical approach alongside both quantitative and qualitative methods, the study also analyses the existing literature on takāyā and their role in delivering humanitarian assistance, as well as in strengthening social solidarity, cooperation, compassion, and altruism among besieged populations residing in displacement camps and charitable takāyā shelters. The findings indicate that Sudanese takāyā play a pivotal role in providing food and medicine to displaced persons, thereby alleviating hunger and ensuring the continuity of daily meals, despite the significant challenges faced by those managing the takāyā. Among these challenges are issues related to fundraising, which require greater public awareness and facilitation to enhance donation-collection efforts. The study further demonstrates the moral and psychosocial impact of takāyā administrators in strengthening social bonds among displaced communities in general, and besieged populations in particular, contributing to the formation of cohesive, cooperative, and mutually supportive communities. This spirit of altruism is reflected in the Qur’anic verse: “They give preference to others over themselves, even though they themselves are in need” (Surah Al-Hashr, 59:9), as well as: “And they give food, despite their love for it, to the needy, the orphan, and the captive” (Surah Al-Insān, 76:8). The study concludes that takāyā can serve as an effective financing and support model for displaced populations in similar conflict zones, such as Palestine in general and Gaza in particular, especially under the severe conditions faced by besieged camps. Achieving this requires concerted efforts and cooperation among charitable practitioners, government bodies, and non-governmental humanitarian organizations to enhance the effectiveness and sustainability of funding provided to takāyā kitchens.